Circulating immunophenotypes are potentially prognostic in follicular cell-derived thyroid cancer - Kotwal, Anupam; Gustafson, Michael P.; Bornschlegl, Svetlana; Dietz, Allan B.; Delivanis, Danae; Ryder, Mabel (Frontiers in Immunology, 2024)
Background: Exploring the immune interface of follicular cell-derived thyroid cancer has prognostic and therapeutic potential. The available literature is lacking for comprehensive immunophenotyping in relation to clinical outcomes. In this study, we identify circulating immunophenotypes associated with thyroid cancer prognosis.Methods: We conducted a pilot observational study of adults with follicular cell-derived thyroid cancer who underwent surgery at our tertiary care referral center and had consented for flow cytometry on peripheral blood collected at the time of thyroidectomy.Results: Of the 32 included subjects, 20 (62%) had well-differentiated, 5 (16%) had poorly differentiated, and 7 (22%) had anaplastic thyroid cancer. The most frequent AJCC stage was 4 (59%) and the ATA risk of recurrence category was high (56%). Patients with AJCC stage 3/4 demonstrated fewer circulating mononuclear cells (CD45+), more monocytes (CD14+), fewer total lymphocytes (CD14-), fewer T cells (CD3+), fewer CD4+ T cells, fewer gamma-delta T cells, fewer natural killer (NK) T-like cells, more myeloid-derived suppressor cells (MDSCs; Lin-CD33+HLADR-), and more effector memory T cells but similar CD8+ T cells compared to stage1/2. Immunophenotype comparisons by ATA risk stratification and course of thyroid cancer were comparable to those observed for stage, except for significant differences in memory T cell subtypes. The median follow-up was 58 months.Conclusions: Aggressive follicular cell-derived thyroid cancer either at presentation or during follow-up is associated with down-regulation of the T cell populations specifically CD4+ T cells, gamma-delta T cells, and NK T-like cells but up-regulation of MDSCs and altered memory T cells signaling. These immunophenotypes are potential prognostic biomarkers supporting future investigation for developing targeted immunotherapies against advanced thyroid cancer.